Consistency of six in situ, in vitro and satellite-based methods to derive chlorophyll a in two optically different lakes - Alikas, Krista; Kangro, Kersti; Kõks, Kerttu-Liis; Tamm, Marju; Freiberg, Rene; Laas, Alo (Frontiers in Environmental Science, 2023)
Phytoplankton and its most common pigment chlorophyll a (Chl-a) are important parameters in characterizing lake ecosystems. We compared six methods to measure the concentration of Chl a (CChl-a) in two optically different lakes: stratified clear-water Lake Saadjärv and non-stratified turbid Lake Võrtsjärv. CChl-a was estimated from: in vitro (spectrophotometric, high-performance liquid chromatography); fluorescence (in situ automated high-frequency measuring (AHFM) buoys)) and spectral (in situ high-frequency hyperspectral above-water radiometer (WISPStation), satellites Sentinel-3 OLCI and Sentinel-2 MSI) measurements. The agreement between methods ranged from weak (R2=0.26) to strong (R2=0.93). The consistency was better in turbid lake compared to the clear-water lake where the vertical and short-term temporal variability of the CChl-a was larger. The agreement between the methods depends on multiple factors, e.g. the environmental and in-water conditions, placement of sensors, sensitivity of algorithms. Also in case of some methods, seasonal bias can be detected in both lakes due to signal strength and background turbidity. The inherent differences of the methods should be studied before the synergistic use of data which will clearly increase the spatial (via satellites), temporal (AHFM buoy, WISPStation and satellites) and vertical (profiling AHFM buoy) coverage of data necessary to advance the research on phytoplankton dynamics in lakes.